2018
DOI: 10.32861/jssr.spi6.986.990
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Lighting in Classroom Environment Influences on Students’ Learning Performance

Abstract: Students learning in educational institutions is associated with classroom environment which normally equipped with physical aspects consists of furniture, air-conditioning, fan, lamp, whiteboard, soft board and etc. The effectiveness and efficiency of learning process in the classroom may not be measured only through the students’ ability and capability, whereas student’s concentration and attention during the lesson also influenced by its physical classroom environment mainly related to indoor lighting. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, this contradicts the findings of previous studies [3,[41][42][43][44][45][46]. For example, Mogas-Recalde & Palau (2021) confirmed the direct impact of classroom lighting on student performance (concentration, attentiveness, achievement, etc.)…”
Section: Environmental Factors (Lnt and Technology) Psychological Hea...mentioning
confidence: 69%
See 1 more Smart Citation
“…However, this contradicts the findings of previous studies [3,[41][42][43][44][45][46]. For example, Mogas-Recalde & Palau (2021) confirmed the direct impact of classroom lighting on student performance (concentration, attentiveness, achievement, etc.)…”
Section: Environmental Factors (Lnt and Technology) Psychological Hea...mentioning
confidence: 69%
“…That is, students with better environmental conditions were found to have better academic performance according to the QEOC questionnaire. Similarly, Norazman et al (2018) discovered that the quality of lighting in the classroom, whether natural or artificial, has an impact on students' achievement, motivation, attendance, skills, concentration, and focus throughout the day [43], and Samani & Samani (2012) showed that there was a significant relationship between lighting quality and student's learning achievement [44]. Along the same line, Gonzales et al (2018) illustrated how intermittent internet disconnection problems negatively affected the GPA of students [45].…”
Section: Environmental Factors (Lnt and Technology) Psychological Hea...mentioning
confidence: 98%
“…Maintaining all three parts ensure building longevity and sustains its value in the future. Moreover, periodic building assessment for school buildings may enhance the building comforts levels, influence a conducive learning environment, and reduce the possibility of critical defects (Norazman et al 2018).…”
Section: The Level Of Satisfaction On School Building Performancementioning
confidence: 99%
“…In most buildings, daylight is a helpful light source, particularly in learning environments such as classrooms, where the quality of natural light is superior to that of any arti cial lighting. Arti cial lighting is required to create a safe and suitable learning environment for students [4]. There is evidence that the quality of room lighting impacts students' learning [5].…”
Section: Introductionmentioning
confidence: 99%